Fibular collateral ligament reconstruction of knee using titanium button: a new fixation technique and an outcome of 35 cases - Rai, Sanjay Kumar; Varma, Rohit; Wani, Sunitkumar (International Journal of Research in Orthopaedics, 2017)
Background: The fibular collateral ligament (FCL) is an important stabilizer of the lateral side of the knee through the whole range of motion. Likewise, it resists external rotation near full extension. Many techniques has been described in the literature for fixation of graft to the fibula like interference screws, making loop around the fibula head but nothing has been said about Titanium button fixation at Fibula end. In our series graft has been fixed at Fibula end using Titanium button. In this article we described our new graft fixation technique. Methods: We included 35 patients all were solider of Indian army and navy who got their knee injured during duties, sport, training and accident, were operated with new technique of graft fixation at Fibula end. Results: As far as my search in the present literature while writing our present study the graft fixation at Fibular end using Titanium button has not yet described by any author. This fixation is robust and results were promising. Out of 35 cases only 02 patients developed knee stiffness and none were has lateral knee opening (Varus stress test was negative). All patients were available for follow up for 18 months. Conclusions: Based on our new technique of the graft fixation at Fibular end using Titanium button we can conclude that this technique is simple and fixation is robust with promising results.